If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(2x + 3) = 0 Reorder the terms: (1 + 2x)(2x + 3) = 0 Reorder the terms: (1 + 2x)(3 + 2x) = 0 Multiply (1 + 2x) * (3 + 2x) (1(3 + 2x) + 2x * (3 + 2x)) = 0 ((3 * 1 + 2x * 1) + 2x * (3 + 2x)) = 0 ((3 + 2x) + 2x * (3 + 2x)) = 0 (3 + 2x + (3 * 2x + 2x * 2x)) = 0 (3 + 2x + (6x + 4x2)) = 0 Combine like terms: 2x + 6x = 8x (3 + 8x + 4x2) = 0 Solving 3 + 8x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + 2x)(1 + 2x) = 0Subproblem 1
Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {-1.5, -0.5}
| u+39=4u | | 3x/5-5x/2 | | x+2y-3z=3 | | 4(x-3)+7=2x | | 2q=q+26 | | 12-0.4t=0 | | 3z=z+48 | | w^2+4=0 | | sin(6x)=3sin(2x) | | 3m^2-5m-372=0 | | 7x^3-10x^2-25x+200=0 | | 9/3*2 | | 9/3x2 | | (Z+5)(z-3)=0 | | 9/3y | | (3x+12)-(2x-4)=0 | | (W+12)(w-2)=0 | | 2x+3x+1=16 | | 2(4)+3(2)(-4)-4(16)= | | y=-8+-1t+-2x+0.5x^2 | | y=0.5x^2+2x-8-4x-t | | 2(x+3)-7=9 | | (4x-5)/4-(2x-1)/6=x | | (2x-4)+(6-x)=0 | | 3(x-1)-4(2x+3)=5 | | (3-x)/6=x/3 | | 3-x/6=x/3 | | (3x^2+5)-(x^2-4x+5)=0 | | 8x^3-104x=0 | | 0.5x^2+2x-8-4x-t=0 | | (m/2)-√5=3 | | (6*5)+3x+22-3x=52 |